HISTORY OF BIOINFORMATICS - Yusupov Ibragim Mirsaydaliyevich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
For today’s students and researchers, it is easy to believe that modern bioinformatics appeared recently to help analyze the next generation of data. However, the beginning of bioinformatics occurred more than 50 years ago, when desktop computers were still hypothesized and DNA could not yet be sequenced. The basis of bioinformatics was laid by the use of computational methods in the analysis of protein sequences in the early 1960s. Subsequently, DNA analysis appeared due to the parallel development of (1) molecular biology methods, which made it easier to synthesize DNA, as well as its sequence and (2) the emergence of increasingly smaller and more powerful computers in Computer Science. It also needed a more appropriate new software to perform bioinformatics functions. From the 1990s to the 2000s, massive improvements in sequential technology have resulted in exponential growth of data along with cost reduction. The emergence of" Big Data "("Big Data") has come up with new challenges in terms of finding and managing data and has required more experience in the field of Computer Science. In combination with constantly increasing bioinformatics tools, biological Big Data (Big Data) has had a profound impact on the predictive power and recurrence of bioinformatics results and continues to do so. To address this problem, universities now fully integrate this science into the curriculum of biology students. Recent junior disciplines such as synthetic biology, System Biology, and whole cell modeling have emerged as a result of an ever-increasing overlap between computer science and biology.